Assessing Student Understanding of Mobile Programming (Android) Competencies - Iwan Adi Prabowo; Hendro Wijayanto; Bramasto Wiryawan (Ittishal Educational Research Journal, 2024)
Mobile programming is a field of study focused on developing applications for mobile devices. While Java is a core language, specific platforms like Android may utilize different frameworks or libraries built upon it. This study aimed to analyze the curriculum of a mobile programming course with an Android focus. The analysis centered on evaluating students' comprehension of the Android-specific materials within the course..The method used is in the form of data collection by interviews and questionnaires by making a list of questions/questionnaires to students related to the material/competence of Mobile programming (Android). The number of respondents is 30 students. The Mobile Programming Materials are as follows: Introduction to Android and Review of Java Programming, Android UI - XML Layout, Activity Life Cycle and Intent, Widgets, Action Bar and Context Menu, Shared Preferences and Files, Audio and Video, Android Advanced UI Design, Implementing Fragment , Broadcast Receivers and Notifications, Location Based Service, Android PHP MySQL. The results of the analysis show that the level of student understanding of mobile programming material is 70% located on the Easy scale. However, it can be seen that the comparison of the average level of student understanding of competency units shows a declining graph, therefore it is necessary to review the curriculum for mobile programming courses in the learning model of each competency unit.